Evaluation of possible inhibition of human liver drug metabolizing cytochromes P450 by two new acetylcholinesterase oxime-type reactivators. (February 2016) - Spicakova, Alena; Anzenbacher, Pavel; Liskova, Barbora; Kuca, Kamil; Fusek, Josef; Anzenbacherova, Eva
Abstract: Two non-symmetric bispyridine oxime – based reactivators of acetylcholinesterase enzyme (AChE), labeled as K027 (1-(4-carbamoylpyridinium)-3-(4-hydroxyiminomethylpyridinium)-propane dibromide) and K203 ((E)-1-(4- carbamoylpyridinium)-4-(4-hydroxyiminomethylpyridinium)-but-2-ene dibromide) were tested for their potential to inhibit activities of human liver microsomal cytochromes P450 (CYP). Both oximes are very potent reactivators of organophosphate-inhibited AChE. An interaction of both compounds with CYP in human liver microsomal preparation was detected using difference spectroscopy. The compounds were shown to bind to CYP enzymes with spectral binding constants of 5.04 ± 1.79 nM (K027) and 5.2 ± 2.6 nM (K203). Enzymology studies were subsequently performed aimed at determining which of the nine most important CYP involved in drug is affected by this interaction. The results have shown no prominent inhibition of individual CYP activities with either compounds except in the case of CYP2E1 and K203. Diagnostic Dixon plot revealed that K203 acted as an uncompetitive inhibitor of CYP2E1. Inhibition of this activity however is not as prominent as to make a potent drug interaction likely. Hence, the interaction of K027 and K203 oxime-type AChE reactivators with human liver microsomal CYP enzymes does not seem to be of prominent clinical importance and both compounds could be safely used in this respect as antidotes with low risk of drug interactions. Highlights: Acetylcholinesterase reactivators were tested for their potential to inhibit P450. Compounds were shown to bind to CYP enzymes. Determining which of the most important CYP is affected was done. No prominent inhibition of CYP activities except CYP2E1 and K203 was found. Both compounds could be safely used with low risk of drug interactions.